E Commerce Dispute Trends Before and After COVID 19: Tren Sengketa E-Commerce Sebelum dan Sesudah COVID-19 - Hardian Sembellagusto; Mochammad Tanzil Multazam (Universitas Muhammadiyah Sidoarjo, 2026)
General Background E-commerce transactions have rapidly expanded in Indonesia, transforming traditional buying and selling into digital interactions that offer efficiency and accessibility. Specific Background The rise of online transactions has been accompanied by increasing consumer disputes, particularly related to fraud, delivery delays, and product discrepancies before and during the COVID-19 pandemic. Knowledge Gap However, limited studies compare dispute patterns across pre-pandemic and post-pandemic periods while considering legal awareness among business actors. Aims This study aims to analyze the development and types of e-commerce disputes and examine their changes before and after the COVID-19 pandemic. Results The findings indicate that although e-commerce usage and transaction volume significantly increased during and after the pandemic, dispute cases decreased due to improved seller awareness, transparency, and service quality. Novelty This study highlights the inverse relationship between transaction growth and dispute reduction by emphasizing the role of business ethics and legal compliance. Implications The results suggest that strengthening legal implementation and promoting awareness among consumers and business actors are essential to ensuring sustainable consumer protection in digital commerce environments. Keywords: E-commerce, Consumer Protection, Legal Disputes, COVID-19, Digital Transactions Key Findings Highlights Dispute cases declined despite significant growth in online transactions Seller transparency and service quality contributed to reduced conflicts Legal awareness played a central role in maintaining consumer trust